Smart energy systems and 4th generation district heating. (1st September 2016) - Lund, Henrik; Duic, Neven; Østergaard, Poul Alberg; Mathiesen, Brian Vad
Abstract: This editorial gives an introduction to the important relationship between Smart Energy Systems and 4th Generation District Heating and presents a number of selected papers from the 1st International Conference on the topic. All of the papers elaborate on or otherwise contribute to the theoretical scientific understanding on how we can design and implement a suitable and least-cost transformation into a sustainable energy future. The concept of Smart Energy Systems emphasizes the importance of being coherent and cross-sectoral when the best solutions are to be found and how this also calls for the active inclusion of the heating and cooling sectors. The concept of 4th Generation District Heating emphasizes that district heating and cooling are both important elements but also technologies that have to be developed further into a 4th generation version to be able to fulfil their roles in future sustainable energy systems. The conclusion is that further development of such theoretical scientific understanding is essential for the implementation of political goals related to future sustainable energy solutions.